1992
DOI: 10.1115/1.2899762
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Wheel Wear in Electrochemical Surface Grinding

Abstract: Major advances in Electrochemical Grinding (ECG) technology depends on new and improved abrasive grain materials. As these new grain materials are developed, proper investigations are necessary to understand the basic behavior of the process by considering significant ECG parameters. This paper presents the ECG study that was conducted to compare both commercially available (standard aluminum oxide and silicon carbide) and newly developed (sintered ceramic grain of aluminum oxide and pure white aluminum oxide)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Dubey et al 26 analyzed the influence of voltage on machining performance of ECG. IIhan et al 27 compared the commercially available and newly developed abrasive grain materials during ECG of 304 stainless steel. They found that wheel wear is mostly initiated by the breakdown of abrasive grains during the machining process.…”
Section: Introductionmentioning
confidence: 99%
“…Dubey et al 26 analyzed the influence of voltage on machining performance of ECG. IIhan et al 27 compared the commercially available and newly developed abrasive grain materials during ECG of 304 stainless steel. They found that wheel wear is mostly initiated by the breakdown of abrasive grains during the machining process.…”
Section: Introductionmentioning
confidence: 99%